Inoculation of Azotobacter vinellandii (SRI Az3) to rice plant increases stress tolerance in rice plant during drought stress - Pradhan, Madhusmita; Sahoo, Ranjan Kumar; Swain, Durga Madhab; Dangar, Tushar Kanti; Mohanty, Santanu (ORYZA-An International Journal of Rice, 2018)
We planted rice plant (Oryza sativa, var. IR 64) with inoculation of Azotobacter vinellandii (SRI Az3) and examined its potency to protect plant from drought stress. We found that it secretes plant growth promoting substances such as IAA, gibberellins, zeatin which helps plant in abiotic stress like drought. The bacteria Azotobacter vinellandii (SRI Az3) significantly promotes the development of root branching, root hairs and primary and secondary lateral roots would increase due to the growth hormones secreted by the Azotobacter spp. along with nitrogen fixation. Agronomic parameters of plants inoculated with Azotobacter vinellandii (SRI Az3) [T4], were studied and compared with rice plants of different treatments [T1, T2 and T3] after drought stress conditions. Endogenous levels of soluble sugar and hormone (GA3, zeatin and IAA) contents were higher in the T4 plants after drought stress condition. The photosynthetic characteristics such as net photosynthetic rate (PN), stomatal conductance (gs), intercellular CO2 (Ci), chlorophyll (Chl) content were significantly higher in T4 after drought stress as compared with plants of other treatments. The activities of antioxidant enzyme viz. malondialdehyde (MDA) and proline content were significantly higher in T4 as compared with plants of other treatments after drought stress. The higher assimilation of endogenous nutrient like nitrogen, potassium, phosphorus, were found as compared to other plants during stress.